PENGARUH INTENSITAS MENGAKSES YOUTUBE TERHADAP AKTIVITAS BELAJAR MAHASISWA FAKULTAS EKONOMI BISNIS TELKOM UNIVERSITY - Raka Adnan Rifhano; Muhammad Sufyan Abdurrahman (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
This research was conducted to find out the effects of intensity in accessing YouTube against the learning activities of students of Economic Business Faculty Telkom University. The purpose of this research is to find out and analyze how big the effects between the intensity of accessing YouTube against learning activities among students of economic Business Faculty Telkom University. These studies use quantitative methods with types of descriptive research-causality. Sampling done by the method of probability sampling which is proportionate stratified random sampling, with the total number of respondents are 100 people. The techniques to analyze data that used in this research is descriptive analysis and simple linear regression analysis. Based on the results of hypothesis testing, the intensity of accessing YouTube has a fairly strong negative effects against learning activities that amount to 22.1%. This is evidenced from the value of the coefficient (r) of 0.470 belonging to the category of a fairly strong relationship tiers. While the rest as much as 77.9% is determined by other variables that are not the focus of this research, such as factors of psychology and family factors. Conclusion from this research indicates that the intensity of accessing YouTube student has done a fairly strong negative effects against the learning activities of students, whether at home or on campus. One example of negative effects is making the students hard to concentrate. This means that the higher of intensity of accessing YouTube that done by students, it has more negative effects to the learning activities of students of Econmic Business Faculty Telkom University.